Impulse Buying Behavior from Monzer Kahf Perpsective - Makarim, Dina Fornia; Nurwahidin, Nurwahidin; Hannase, Mulawarman (ITB AAS INDONESIA Surakarta, 2024)
Impulse buying behavior is closely related to sudden purchases without careful consideration and ignoring alternatives or future implications that are influenced by the temptation to satisfy momentary emotions. It is also related to the use of wealth for wants rather than needs, while human desires are unlimited. This study aims to review the impulse buying behavior and its factors, furthermore, how Islamic consumption norms can lead to resolve the behavior, particularly from Monzer Kahf perspective. The analytical method in this research is literature study by presenting related datas and theories arranged systematically. The results of this study indicate that impulse buying behavior is in contrast to the concept of Islamic consumption norms, as has been explained in detail by one of the 20th century Islamic economists, Monzer Kahf.